Philosophy of State: Leviathan and State Power according to Thomas Hobbes - Nur Rohim Yunus (ADALAH, 2019)
One of the most influential philosophers in history is Thomas Hobbes, who lived in Great Britain during the 17th century. Hobbes is a supporter of social contract ethics, which is the idea that the moral and political obligations of individuals depend on contracts or agreements between them to form the community where they live. During his life, Hobbes published many different works about political theory, philosophy, and history. The most famous work written by Thomas Hobbes was "Leviathan", written in 1651 in response to the British civil war, which resulted in the formation of a parliamentary system and reducing monarchy power. Although Hobbes rejected the King's divine rights to govern his citizens. But in Leviathan's theory he stated that to guarantee shared salvation, an agreement needs to be made and eliminating the absolute natural rights of humans. You do this by creating political authority that has coercive power (absolute power) to force people to submit to social agreements. Where the agreement was carried out between humans, they surrendered all of their sovereignty to The Sovereign (Public Authority).